THE DECONSTRUCTIVE SEMIOTICS OF FISHING MANTRA DICTION IN THE BAJO ETHNICS - Rita Lindayani, Lilik; Suarka, I Nyoman; Cika, I Wayan; Kebayantini, Ni Luh Nyoman; Putra, Ansor; Samsul, Samsul; Maliudin, Maliudin (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2018)
Language is a form of human emergency sensitivity to the situation around it. If observed, if the linguistic position is in the semiotic point pattern, then natural signs can be a form of verbal power. Accompanying Nietzsche's thoughts on a strategy he calls